2019
DOI: 10.1177/0743558419883359
|View full text |Cite
|
Sign up to set email alerts
|

“It’s Just the Thing You Do”: Physical and Digital Fields, and the Flow of Capital for Young People’s Gendered Identity Negotiation

Abstract: This article examines young people’s negotiation of their identities in relation to gender. We explore this through two important sites for young people—physical relationships in the school environment and mainstream social media sites (e.g., Instagram and Facebook)—with the suggestion that social media is an important site for young people that permits discursive and identity exploration. Specifically, we use a Bourdieusian framework to examine the flow of capital between fields as well as the identities that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
(115 reference statements)
0
9
1
Order By: Relevance
“…In particular, as in the work of Pullen (2010) and Downing (2013) I have highlighted the importance of the community that is present online and who support WLW in feeling both valued and praised; thus, indicating that these experiences may be absent from WLW's physical worlds. This is different from research on normative populations that suggests physical and offline worlds are co-constitute (e.g., Byron et al, 2013;Metcalfe & Llewellyn, 2020). It is evident from my survey that the physical world does not operate as a safe or queer centric place for WLW, this instead can be provided by the online world and particular spaces within it.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In particular, as in the work of Pullen (2010) and Downing (2013) I have highlighted the importance of the community that is present online and who support WLW in feeling both valued and praised; thus, indicating that these experiences may be absent from WLW's physical worlds. This is different from research on normative populations that suggests physical and offline worlds are co-constitute (e.g., Byron et al, 2013;Metcalfe & Llewellyn, 2020). It is evident from my survey that the physical world does not operate as a safe or queer centric place for WLW, this instead can be provided by the online world and particular spaces within it.…”
Section: Discussioncontrasting
confidence: 74%
“…LGBTQ and online space Usage of new media is integrated into our everyday lives (Livingstone, 2008). Moreover, recent research (Byron, Albury, & Evers, 2013;Metcalfe & Llewellyn, 2020) suggests there is flow between the physical and online worlds in terms of identity construction. As such, structural and social categories that are found in the physical world are often replicated, or have precedence, online.…”
Section: Background Literature and Contextmentioning
confidence: 99%
“…For example, researchers have analyzed Facebook posts and photos to examine how social media use can objectify and sexualize female athletes (Frederick et al, 2017), and Barnett (2017) found that while female athletes posted content online to demonstrate their commitment to sport, they nevertheless followed traditional gender scripts and stereotypes such as appearing nurturing and loving, but also submissive and docile (Barnett, 2017). These gender norms have also been demonstrated in nonsport populations, with research indicating that adolescents receive additional "social capital" (e.g., more "likes" on social media and perceived popularity), when their identity displays online were consistent with gender stereotypes of masculinity and femininity (MetCalfe & Llewellyn, 2020). Other studies examining social media use among college athletes has found that athletes who engage more with teammates via social media identified more strongly with their sports team (Kim & Kim, 2019).…”
Section: Social Media and Electronic Communication In Young Peoplementioning
confidence: 99%
“…Adolescents' attraction to electronic communication has been attributed to its features that allow greater controllability of self-presentation and disclosure compared to face-to-face communication (Valkenburg & Peter, 2013), which may be helpful for adolescents trying to accrue social capital or make more friends, particularly when there is congruence between their on-line and in-person identity (MetCalfe & Llewellyn, 2020). For example, electronic communication allows one to choose which audiovisual cues to share or hide (i.e., choosing to send only written texts without speaking verbally or showing their face), and one has the freedom and time to edit their message prior to sending it.…”
Section: Social Media and Electronic Communication In Young Peoplementioning
confidence: 99%
“…Some youth may have multiple online screennames and roles that they perform depending on the audience. At the same time, many youth feel pressure to present an online identity that mirrors their offline identity, particularly on platforms popular with their peer group, such as Instagram [70]. Even on these apps, however, youth are finding ways to present different aspects of themselves.…”
Section: Identity and Learning Online And Offlinementioning
confidence: 99%